The motivating role of positive feedback in sport and physical education: Evidence for a motivational model - Mouratidis, A.; Vansteenkiste, M.; Lens, W.; Sideridis, G. (Journal of Sport & Exercise PsychologyJournal of Sport & Exercise Psychology, 2008)
Based on self-determination theory (Deci & Ryan, 2000), an experimental study with middle school students participating in a physical education task and a correlational study with highly talented sport students investigated the motivating role of positive competence feedback on participants' well-being, performance, and intention to participate. In Study 1, structural equation modeling favored the hypothesized motivational model, in which, after controlling for pretask perceived competence and competence valuation, feedback positively predicted competence satisfaction, which in turn predicted higher levels of vitality and greater intentions to participate, through the mediation of autonomous motivation. No effects on performance were found. Study 2 further showed that autonomous motivation mediated the relation between competence satisfaction and well-being, whereas amotivation mediated the negative relation between competence satisfaction and ill-being and rated performance. The discussion focuses on the motivational role of competence feedback in sports and physical education settings.